Sustaining Lake Toba’s Tourism: Role of Creative Industry, Green Tourism Marketing and Tourism Experience - Lumbaraja, Prihatin; Lubis, Arlina Nurbaity; Hasibuan, Beby Kendida (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper. Research aims: This study aims to investigate the role of creative industry, green tourism marketing and tourist experience in building tourists’ satisfaction. Design/Methodology/Approach: Data were collected from 200 tourists who visited Lake Toba, Indonesia; and then analysed using structural equation modelling. Research findings: The findings indicate that green tourism marketing and creative industry are positively related to tourism experience. This study, however, does not find substantial evidence to support the direct relationship between green tourism marketing and creative industry with tourism satisfaction. Instead the relationship is mediated by tourism experience. Theoretical contribution/Originality: The findings indicate that green tourism marketing and creative industry are positively related to tourism experience. This study, however, does not find substantial evidence to support the direct relationship between green tourism marketing and creative industry with tourism satisfaction. Instead the relationship is mediated by tourism experience. Practitioner/Policy implications: This study provides insights for marketers and policy makers to better understand how tourism in Lake Toba can be sustained. It specifically highlights the role of creative tourism and green tourism marketing in creating exciting tourism experience and tourism satisfaction. This outcome is expected to facilitate tourism operators in sustaining their businesses and for policy makers to consider this as a strategy for decision-making. Research limitation: Since this study focusses on the Lake Toba tourism industry only, the generalisability of the findings may be biased. Therefore, future studies should incorporate a larger and more diverse set of samples. Keywords: Tourism Satisfaction, Tourism Experience, Creative Industries, Green Tourism Marketing, Developing Country, Indonesia JEL Classification: M3